Recent Advances and Prospects in the Research of Nascent Adhesions - Henning Stumpf, Bernd; Ambriović-Ristov, Andreja; Radenovic, Aleksandra; Smith, Ana-Sunčana (Frontiers in Physiology, 2020)
Nascent adhesions are submicron transient structures promoting the early adhesion of cells to the extracellular matrix. Nascent adhesions typically consist of several tens of integrins, and serve as platforms for the recruitment and activation of proteins to build mature focal adhesions. They are also associated with early stage signalling and the mechanoresponse. Despite their crucial role in sampling the local extracellular matrix, very little is known about the mechanism of their formation. Consequently, there is a strong scientific activity focused on elucidating the physical and biochemical foundation of their development and function. Precisely the results of this effort will be summarized in this article.